Immune and Inflammatory Properties of Megakaryocytes - Shiv Vardan Singh; Audrey Lucerne; Katya Ravid (Cells, 2025)
Megakaryocytes (MKs), which primarily develop in bone marrow (BM) from hematopoietic stem cells, are critical for platelet production. Beyond their well-established role in thrombopoiesis, MKs have been identified as important for BM niche maintenance, such as by supporting the growth and differentiation of other cell types. Recently, megakaryopoiesis has been reported as yielding divergent subpopulations of MKs, as evidenced by single-cell RNA sequencing of lung, spleen, or BM resident MKs. Interestingly, these subpopulations constitute a significant proportion of “immune MKs” expressing various classical immune markers and capable of phagocytosing pathogens and contributing to antigen presentation. As such, MKs were also found to regulate inflammation, mainly by secreting various cytokines and chemokines to crosstalk with other cell types. The level and functional signature of these “immune MKs” were found to be altered in various pathological conditions, indicative of their purposeful values in health and diseases. In this review, we survey and highlight newly reported functional immune and inflammatory properties of MKs in health and in select pathologies.